2016
DOI: 10.1038/gim.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of a cohort with clinical diagnosis of familial hypercholesterolemia: considerations for genetic diagnosis improvement

Abstract: Purpose: Familial hypercholesterolemia (FH) is a common autosomal dominant disorder of lipid metabolism caused by mutations in LDLR, APOB, and PCSK9. To fulfill the World Health Organization recommendation, the Portuguese FH Study was established. Here, we report the results of the past 15 years and present practical considerations concerning the genetic diagnosis of FH based on our experience. Methods:Our approach comprises a biochemical and molecular study and is divided into five phases, including the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
(51 reference statements)
2
26
1
1
Order By: Relevance
“…ADH due to "gain of function" PCSK9 mutations is uncommon, occurring in less than 1% of cases (9)(10)(11). Note that PCSK9 inhibitors are a promising new class of drugs for LDL-C reduction ( 20,21 ).…”
Section: Supplementary Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…ADH due to "gain of function" PCSK9 mutations is uncommon, occurring in less than 1% of cases (9)(10)(11). Note that PCSK9 inhibitors are a promising new class of drugs for LDL-C reduction ( 20,21 ).…”
Section: Supplementary Abstractmentioning
confidence: 99%
“…LDLR is the gene most frequently associated with ADH and is also the best characterized. It is responsible for the disease called familial hypercholesterolemia (FH) (9)(10)(11). With the exception of a few founder populations, the spectrum of LDLR causing FH mutations is large.…”
Section: Supplementary Abstractmentioning
confidence: 99%
“…The observed elevated prevalence of APOB mutations (particularly the 34 specific mutations), in accordance with the report from Yang et al 34 showing that 18 out of 30 families were identified by harboring LDLR or APOB mutations with frequencies of 77.8% (14/18) and 22.2% (4/18), respectively, might indicate an important gene effect of APOB mutations on Chinese FH. Moreover, investigators from Taiwan and other ethnicities have suggested recently that the number of APOB mutations is increasing, 16,36 most notably in Taiwan. 34,38 The elevated prevalence of APOB mutations among Chinese patients might be possible, as pointed out by Andersen et al 38 Additionally, most currently available genetic testing in APOB is focused on exon 26 and p.Arg3500Trp rather than on the entire coding region.…”
Section: Et Al Familial Hypercholesterolemia In China 577mentioning
confidence: 99%
“…40,41 Therefore, it may be beneficial to undertake sequencing of the entire APOB gene because other rare variants in the gene may be responsible for the patient's clinical phenotype. 36,39 In the present study, we screened the whole exons in APOB and found some mutations in nonhot region. The hot exon of 26 showed a frequency of 37.8% in APOB mutations.…”
mentioning
confidence: 99%
“…Autosomal dominant FH is attributed to mutations in three different genes: LDL receptor (LDLR), APOB, and proprotein convertase subtilisin/kexin type 9 (PCSK9) (1,(3)(4)(5). Other FH genes have been searched for using exome sequencing without success (2).…”
mentioning
confidence: 99%